Designing a Virtual Exchange Intervention for the Development of Global Competence: An Exploratory Study - Nicolaou, Anna (My University, 2020)
This study demonstrates the process of designing a virtual exchange intervention aiming at developing English for Specific Purposes (ESP) learners’ global competence. The study adopted a three-phase Design-Based Research (DBR) approach which included the exploration phase, the implementation phase, and the reflection phase. In this paper, the exploration phase of the study is presented, which was conducted in order to gain insight on various aspects pertaining to virtual exchange embedded in ESP learning. The study was formulative in nature as it aimed to examine the feasibility of the intervention and determine the best intervention design. It also aimed at examining students’ attitudes towards telecollaborative learning, their perceptions regarding the anticipated benefits and challenges of virtual exchange, as well as their suggestions concerning the implementation of the intervention. The study combined a mixed methods approach with secondary data collection through a review of similar studies, quantitative data collection by means of an opinion questionnaire, and qualitative data collection through focus groups with university students. The findings of the research provided a thorough understanding of the design of virtual exchange and formed the basis of a more conclusive subsequent study.
Keywords: DBR; Exploratory study; Global competence; Virtual exchange